2014
DOI: 10.3324/haematol.2013.091272
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of switching to nilotinib 400 mg twice daily for patients with chronic myeloid leukemia in chronic phase with suboptimal response or failure on front-line imatinib or nilotinib 300 mg twice daily

Abstract: ABSTRACTdifferent therapy "whenever available and applicable". 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…In the Hughes et al study, 4 the authors note adverse events with switch from imatinib to nilotinib were in line with prior phase II studies, including approximately 10% discontinuation for AEs. In the ENESTcmr study, 10 however, with 36 mos of follow up, authors noted that for those patients switching to nilotinib, rates of AEs and related treatment discontinuation were higher in addition to a numerically higher amount of cardiovascular events observed with nilotinib.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…In the Hughes et al study, 4 the authors note adverse events with switch from imatinib to nilotinib were in line with prior phase II studies, including approximately 10% discontinuation for AEs. In the ENESTcmr study, 10 however, with 36 mos of follow up, authors noted that for those patients switching to nilotinib, rates of AEs and related treatment discontinuation were higher in addition to a numerically higher amount of cardiovascular events observed with nilotinib.…”
supporting
confidence: 58%
“…In the ENESTnd trial and forming the basis for the extension study reported herein by Hughes et al, 4 the occurrence of suboptimal response at earlier time points (6 and 12 mos), again reflecting incomplete cytogenetic response, was modest across the study but more common in the imatinib cohort. Suboptimal response at 18 mos, now reflecting incomplete molecular response, was observed much more often (approx.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are data to suggest that nilotinib dose escalations or reductions, as necessary, can be beneficial for some patients, maximizing both efficacy and tolerability (Rosti et al , 2009; Hughes et al , 2014b; Gugliotta et al , 2015). An ENESTnd extension study evaluated the impact of nilotinib dose escalation in a small cohort of patients ( n  = 19) with suboptimal response or treatment failure on nilotinib 300 mg twice daily; among patients who had not achieved a complete cytogenetic response (CCyR) or MMR at the time of dose escalation, approximately one‐third [33% (2 of 6) and 39% (7 of 18), respectively] achieved CCyR and MMR, respectively, on nilotinib 400 mg twice daily by the data cut‐off (median follow‐up after dose escalation, 19 months) (Hughes et al , 2014b).…”
mentioning
confidence: 99%
“…An ENESTnd extension study evaluated the impact of nilotinib dose escalation in a small cohort of patients ( n  = 19) with suboptimal response or treatment failure on nilotinib 300 mg twice daily; among patients who had not achieved a complete cytogenetic response (CCyR) or MMR at the time of dose escalation, approximately one‐third [33% (2 of 6) and 39% (7 of 18), respectively] achieved CCyR and MMR, respectively, on nilotinib 400 mg twice daily by the data cut‐off (median follow‐up after dose escalation, 19 months) (Hughes et al , 2014b). Additionally, an independent study of frontline nilotinib 400 mg twice daily in patients with newly diagnosed CML‐CP demonstrated the feasibility of managing adverse events (AEs) and laboratory abnormalities with nilotinib dose reductions (Rosti et al , 2009; Gugliotta et al , 2015).…”
mentioning
confidence: 99%